Diagnosis, evaluation, and management of the hypertensive disorders of pregnancy: executive summary - Magee, Laura A.; Pels, Anouk; Helewa, Michael; Rey, Evelyne; Dadelszen, Peter von (REPRODUCTIVE ENDOCRINOLOGY, 2014)
This executive summary presents in brief the current evidence assessed in the clinical practice guideline prepared by the Canadian Hypertensive Disorders of Pregnancy Working Group and approved by the Executive and Council of the Society of Obstetricians and Gynaecologists of Canada to provide a reasonable approach to the diagnosis, evaluation, and treatment of the hypertensive disorders of pregnancy. Evidence: Published literature was retrieved through searches of Medline, CINAHL, and The Cochrane Library in March 2012 using appropriate controlled vocabulary and key words. Results were restricted to systematic reviews, randomized control trials, controlled clinical trials, and observational studies published in French or English between January 2006 and February 2012. Searches were updated on a regular basis and incorporated in the guideline to September 2013